Saliva-derived exosomes regulate fibroblast metabolic reprogramming in skin wound healing - Sijia Song; Sijia Song; Sijia Song; Sijia Song; Rong Xiang; Rong Xiang; Rong Xiang; Rong Xiang; Siyu Chen; Siyu Chen; Siyu Chen; Siyu Chen; et al. (Frontiers in Cell and Developmental Biology)
BackgroundEffective skin repair requires rapid wound closure accompanied by precise extracellular matrix (ECM) remodeling and balanced cellular metabolism. Saliva-derived exosomes (S-Exo) have emerged as promising therapeutic agents due to their rich bioactive components; however, their mechanisms in ECM remodeling and metabolic regulation remain unclear. This study aimed to elucidate how S-Exo modulate ECM turnover through metabolic reprogramming, particularly glycolysis, in human skin fibroblasts (HSFs), and identify critical exosomal molecules mediating these effects.MethodsS-Exo were isolated and characterized. A rat full-thickness skin defect model and in vitro assays with human skin fibroblasts and HaCaT keratinocytes were employed to evaluate S-Exo effects on wound closure, ECM remodeling, and cellular metabolism. Transcriptomic profiling of wound tissues, targeted metabolomic analysis of fibroblasts, and proteomic evaluation of S-Exo cargo were performed to explore underlying mechanisms. Metabolic interventions further confirmed the contribution of metabolic modulation to S-Exo-mediated wound healing.ResultsS-Exo significantly accelerated wound healing by enhancing fibroblast viability, migration, and ECM remodeling, characterized by elevated secretion of matrix metalloproteinases (MMP1 and MMP3). Transcriptomic, metabolomic, and proteomic analyses revealed that S-Exo robustly activated key metabolic pathways, particularly glycolysis, reflected by increased expression of glycolytic genes (e.g., GLUT1, HK2, PFKM) and enhanced glycolytic flux in fibroblasts. Remarkably, S-Exo were found to carry nearly all enzymes involved in glycolysis, indicating an underlying enzyme-transfer mechanism for sustained metabolic modulation. Importantly, glycolytic activity positively correlated with MMP secretion, and inhibition of glycolysis significantly reduced MMP production, highlighting glycolysis as a crucial regulator of ECM remodeling.ConclusionSaliva-derived exosomes promote wound healing by potentially modulating fibroblast metabolism via exosome-associated glycolytic enzymes, enhancing glycolytic flux, and thereby regulating ECM remodeling via increased MMP secretion. These findings provide novel insights into metabolism-targeted exosome therapies for wound healing.